2011
DOI: 10.1111/j.1468-3083.2011.04391.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rituximab treatment in Indian pemphigus patients

Abstract: Rituximab is effective in treating resistant and severe pemphigus in Indian patients. Acute complications can occur during rituximab infusion and require close monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
74
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 33 publications
7
74
1
Order By: Relevance
“…The association between shorter disease duration and higher rate of CR might support the rationale for using RTX as a first-line treatment in pemphigus, even for treatment-naïve patients (12,19,24,31,39). Lunardon et al (12) also suggested that treatment with RTX earlier in the course of disease might result in better outcomes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The association between shorter disease duration and higher rate of CR might support the rationale for using RTX as a first-line treatment in pemphigus, even for treatment-naïve patients (12,19,24,31,39). Lunardon et al (12) also suggested that treatment with RTX earlier in the course of disease might result in better outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…However, there is no universally accepted protocol for its use in pemphigus. Several commonly used regimens include a lymphoma protocol (4 weekly infusions of RTX at a dose of 375 mg/m 2 ) (4-17), a rheumatoid arthritis (RA) protocol (2×1,000 mg doses of RTX at a 2-week interval) (10,12,(18)(19)(20)(21), low-dose RTX (2×500 mg doses of RTX at a 2-week interval) (10,16,(21)(22)(23)(24) with or without concomitant use of IA (9,10,(25)(26)(27)(28)(29) or IVIG (30). RTX has also been used as a first-line treatment with favourable outcomes (12,31).…”
mentioning
confidence: 99%
“…Relapse rates in the literature range between 0 and 53% [10,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. Three studies using the 1,000 mg biweekly regimen report lower relapse rates (0-22%) [28,30,32]. A randomized study could verify whether there is indeed superiority of the biweekly regimen in relapse rates.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of rituximab in pemphigus vulgaris was initially described in 2002, and since then several studies have been presented in the literature [10,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32] (table 2). In 95% of patients treated, at least partial remission is achieved as summarized in a meta-analysis by Schmidt et al [33].…”
Section: Discussionmentioning
confidence: 99%
“…The mean TDC in various earlier studies using rituximab with concomitant oral corticosteroids ranged from 6 to 8 weeks [14,15] .…”
Section: Discussionmentioning
confidence: 99%